SENTIMENT ANALYSIS OF CUSTOMER PRODUCT REVIEWS USING MACHINE LEARNING - M V Keerthi, O. Chandana, P. Anjali, P. Revathi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Today, digital reviews play a pivotal role in enhancing global communications among consumers and influencing consumer buying patterns. commerce giants like Amazon, Flipkart, etc. provide a platform to consumers to share their experience and provide real insights about the performance of the product to future buyers. In order to extract valuable insights from a large set of reviews, classification of reviews into positive and negative sentiment is required. Sentiment Analysis is a computational study to extract subjective information from the text. In the proposed work, over 4,000,00 reviews have been classified into positive and negative sentiments using Sentiment Analysis. Out of the various classification models, Naïve Bayes, Support Vector Machine (SVM) and Decision Tree have been employed for classification of reviews. The evaluation of models is done using 10-Fold Cross Validation.